Bridging the Gap in Facial Aesthetic Surgery Training: A National Survey Study of Canadian Resident and Program Director Perspectives on Resident-Run Clinics in Otolaryngology Residency Programs - Shapiro, Justin; Zgardau, Alina; Khoury, Sami; Moore, Corey (Facial Plastic Surgery, 2025)
Resident-run facial aesthetic surgery clinics improve surgical proficiency but are absent in Canadian Otolaryngology–Head and Neck Surgery (OtoHNS) training.To evaluate resident and program director (PDs) perspectives on facial aesthetic training and the feasibility of resident-run clinics. We hypothesized residents would report inadequate training and support for clinics, while directors would express caution due to logistical barriers.National, cross-sectional survey.Anonymous, bilingual electronic surveys were distributed to Canadian OtoHNS residents and PDs. Quantitative data were analyzed descriptively; qualitative responses underwent thematic analysis.Fifty residents and 11 PDs responded. Most residents (91%) reported performing ≤ 5 core procedures; 82% desired more exposure. Resident-run clinics were supported by 83% of residents but only 30% of PDs. PDs cited supervision, funding, and legal concerns.Significant training gaps exist. Resident-run clinics may enhance education but require structured supervision and institutional support.
Keywords: aesthetic surgery; resident-run clinics; otolaryngology; surgical education